Kompleksitas Suara Ester: Negosiasi Subaltern atau Privilese? - Setiawan, Yohanes (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
Marginalized groups are often denied an authentic voice within dominant power structures. This issue is relevant to understanding representation, power, and inequality in different social, political, and cultural contexts. This article seeks to explore the complexities of Esther's representation and identity from the perspectives of the subaltern and liberation theology. It critically examines Gayatri Chakravorty Spivak's question,